Espaços sonoros : a experiência sónica no contexto da arte pública - Carvalho, José Vasco Gaio Monteiro Barroco (2019)
The increasing complexity and size of contemporary cities incited the necessity to rethink the experience and aesthetic of living in a public space. In this context, public art first appeared as an integrating element, capable of deepening the collective memories of communities, to later evolve towards a thematic centered around the globalized individual. In that sense, globalized cities promote a fertile ground for understanding the fundamental questions regarding the conceptual, functional and aesthetic relationship between individuals and the public space they inhabit. The work presented in this doctoral research relates the social and artistic experience of western contemporary cities with their aural culture. This work presents the progression of the use of sound in art and seeks to demonstrate the relevance of sound as a sociological phenomenon, important in the connection between the individual and the inhabiting space. The research begins with the identification of the distinct strategies and methods for implementing sonic interfaces in public art and of the direct use of quotidian sounds as a support and basis for the construction of different artistic expressions such as audio-visual sound design, artistic sound spaces, compositions by soundscapes and sound sculptures. This study surfaced evidences regarding the potential and effectiveness of the use of multimedia technology in the context of sonic ecology projects for moderating the interaction between the occupant, the environment and identity of the public space. In order to further explore and verify this idea, a set of artistic experiences situated in the context and thematic of “place” were developed using distinct technological implementation strategies. A qualitative analysis of the work, through interviews and surveys taken on by curators and coauthors, concluded that the use of technology was indeed efficient in the resolution of conceptual and technical requirements of the artistic development, and that modern mobile technology such as sonic augmented reality is successful in transforming the experience of the public space using everyday sounds.